2021
DOI: 10.1038/s41419-021-04413-0
|View full text |Cite
|
Sign up to set email alerts
|

LAMTOR5-AS1 regulates chemotherapy-induced oxidative stress by controlling the expression level and transcriptional activity of NRF2 in osteosarcoma cells

Abstract: Long-noncoding RNAs (lncRNAs) play roles in regulating cellular functions. High-throughput sequencing analysis identified a new lncRNA, termed LAMTOR5-AS1, the expression of which was much higher in the chemosensitive osteosarcoma (OS) cell line G-292 than in the chemoresistant cell line SJSA-1. Further investigations revealed that LAMTOR5-AS1 significantly inhibits the proliferation and multidrug resistance of OS cells. In vitro assays demonstrated that LAMTOR5-AS1 mediates the interaction between nuclear fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Functional experiments showed that overexpression of ENTPD3-AS1 inhibited cell proliferation in renal cancer cell lines 64 . Pu et al found that LAMTOR5-AS1 could markedly impair the proliferation of osteosarcoma cells 65 . Lin et al found that Linc01278 inhibited the cell proliferation of papillary thyroid cancer by impelling apoptosis and mitigated the effects of cancer cells migration and invasion by regulating the EMT process 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Functional experiments showed that overexpression of ENTPD3-AS1 inhibited cell proliferation in renal cancer cell lines 64 . Pu et al found that LAMTOR5-AS1 could markedly impair the proliferation of osteosarcoma cells 65 . Lin et al found that Linc01278 inhibited the cell proliferation of papillary thyroid cancer by impelling apoptosis and mitigated the effects of cancer cells migration and invasion by regulating the EMT process 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we used the starBase v2.0 database to predict that LAMTOR5-AS1 regulates the expression of TP63 in OS through the ceRNA mechanism in combination with hsa-miR-23a-3p. Pu et al (42) demonstrated that LAMTOR5-AS1 reduces OS cell growth and multidrug resistance in a considerable way. In this study, LAMTOR5-AS1 knockdown decreased the expression of cleaved-Caspase-1, cleaved-Caspase-3, cleaved-Caspase-4, cleaved-Caspase-8, GSDME, and GSDMD-N in OS cells, which demonstrated that the type and expression trend of pyroptosis marker proteins regulated by LAMTOR5-AS1 was consistent with those regulated by TP63.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PRDX4, PRDX1, and MGST1 all have antioxidant capacities with their ROS scavenging abilities [ 159 , 160 , 161 ]. LAMTOR5 mediates the interaction between NRF2 and KEAP1, which regulates oxidative stress, as shown in osteosarcoma cells [ 162 ]. It has been reported that defects in the FTL cause an increase in iron levels and, thus, oxidative stress, contributing to neurodegeneration in mice.…”
Section: The Transcriptomic Landscape Of the Oxidative Stress Pathway...mentioning
confidence: 99%